2007
DOI: 10.1183/09031936.00034507
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy improves low performance status lung cancer patients

Abstract: The aim of the present study was to determine the potential benefit of conventional cisplatin-based chemotherapy on patients with advanced nonsmall cell lung cancer (NSCLC) and poor performance status (PS), defined as 60-70 on the Karnofsky scale.Retrospective analysis was carried out of a randomised trial performed in advanced NSCLC where 485 patients received three courses of gemcitabine+ifosfamide+cisplatin induction chemotherapy.Of the patients, 80% had good PS (Karnofsky 80-100) and 20% poor PS. Response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…In a subgroup analysis based on two randomized parallel trials of mitomycin, ifosfamide and cisplatin administered to ANSCLC patients [31], the most significant HRQOL improvements during chemotherapy was observed in the PS 2 rather than the PS 0/1 group [6]. Clinical improvement, defined as achieving a good PS during combination chemotherapy, is observed in ANSCLC patients with poor PS [32]. The better palliation among PS 2 patients in the present study may reflect their heavier symptom and disease burden and thus a greater potential for palliation.…”
Section: Discussionmentioning
confidence: 91%
“…In a subgroup analysis based on two randomized parallel trials of mitomycin, ifosfamide and cisplatin administered to ANSCLC patients [31], the most significant HRQOL improvements during chemotherapy was observed in the PS 2 rather than the PS 0/1 group [6]. Clinical improvement, defined as achieving a good PS during combination chemotherapy, is observed in ANSCLC patients with poor PS [32]. The better palliation among PS 2 patients in the present study may reflect their heavier symptom and disease burden and thus a greater potential for palliation.…”
Section: Discussionmentioning
confidence: 91%
“…Also, there was neither socio-demographical nor clinical characteristics difference between responders vs non responders. Second, previous studies showed poor performance status associated with worse survival and good performance with better survival [15,16,35]. We had information on treatments that were performed after the HRQoL measurement and we assumed, according to standards, that these treatments were prescribed in accordance with each patient’s condition, integrating performance status.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some authors have argued that chemotherapy for stage IV patients should be limited to patients with ECOG performance status 0 or 1 [9]; however, other publications suggest that some patients with PS 2 may also benefit from treatment [10]. Female sex is also a quite reproducible factor and this has recently been confirmed by a meta-analysis [11].…”
Section: Classical Host-related and Tumour-related Factorsmentioning
confidence: 98%